Magnified Endoscopic Findings of Multiple White Flat Lesions: A New Subtype of Gastric Hyperplastic Polyps in the Stomach - Rino Hasegawa; Kenshi Yao; Shoutomi Ihara; Masaki Miyaoka; Takao Kanemitsu; Kenta Chuman; Go Ikezono; Akikazu Hirano; Toshiharu Ueki; Hiroshi Tanabe; Atsuko Ota; Seiji Haraoka; et al. (Korean Society of Gastrointestinal Endoscopy, 2018)
Background/Aims: While the occurrence of multiple whitish flat elevated lesions (MWFL) was first reported in 2007, no studies on MWFL have been published to date. The present retrospective observational study aimed to clarify the endoscopic findings and clinicopathological features of MWFL. Methods: Subjects were consecutive patients who underwent upper gastrointestinal endoscopy as part of routine screening between April 2014 and March 2015. The conventional white-light, non-magnifying and magnifying narrow-band images were reviewed. Clinical features were compared between patients with and without MWFL. Results: The conventional endoscopic findings of MWFL include multiple whitish, flat, and slightly elevated lesions of various sizes, mainly located in the gastric body and fundus. Narrow-band imaging enhanced the contrast of MWFL and background mucosa, and magnifying narrow-band imaging depicted a uniformly long, narrow, and elliptical marginal crypt epithelium with an unclear microvascular pattern. Histopathological findings revealed hyperplastic changes of the foveolar epithelium, and parietal cell protrusions and oxyntic gland dilatations were observed in the fundic glands, without any intestinal metaplasia. The rate of acid-reducing drug use was significantly higher in patients with MWFL than in those without (100% [13/13] vs. 53.7% [88/164], p<0.001). Conclusions: The present study indicated a relationship between the presence and endoscopic features of MWFL and history of acidreducing drug use.